BA (Hons) Interior Design 2025-26 - Olsson, Gina (University of Edinburgh, 2026)
Annual programme catalogue documenting the work of the BA (Hons) Interior Design programme at ESALA, ECA. This catalogue showcases work from across the programme, and individual graduate projects from the 2025-26 academic year.
Keywords: ESALA; Interior Design